(3aQU h JMOjGJ GdfXGe GdeUQaj GdLRGFQj aj Xd eJZjQGJ GdHjFI GdeUQajI GdOhdjI (B/s - (3eYeQ, aWhes; (3ZQHj, jSjf Sj dGNVQs ((3GdLRGFQ(B: s (3OGQ GdCLjGd GdQbej(B, s, 2023)
(3GdfXGe GdeGdj cOYGeI CSGSjI ddfXGe GdeUQaj,hCSGSjGJ Mhd GdfXGe GdeUQaj, cPdc fTCJg hJWhQg, EVGaI Edi GdJhLgGJ GdMOjKI ddfXGe GdeUQaj GdLRGFQj, hBdjGJ YUQfJg, cPGdc OYe JHfj GdUjQaI GdGSdGejI aj GdfXGe GdeUQaj GdLRGFQj, hGdeDSSGJ GdfbOjI hGdOhdjI h UfOhb GdfbO GdOhdj, eaGgjeg hCSSg(B.s
(3eQGLY U(B.209-228s
Keywords: (3GdHfhc GdJLGQjIs; (3GdHfhc GdOhdjIs; (3GdHfhc(B- (3GdLRGFQs